2001
DOI: 10.1046/j.1365-2540.2001.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of population disjunction on isozyme variation in the widespread Pilgerodendron uviferum

Abstract: Geographical range is considered a good predictor of the levels of isozyme variation in plants. Widespread species, often consisting of historically larger and more continuous populations, maintain higher polymorphism and are less aected by drift, which tends to erode genetic variation in more geographically restricted species. However, widespread species occurring in small and disjunct populations may not ®t this pattern. In this study we examined genetic variation in Pilgerodendron uviferum, a conifer endemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 25 publications
1
39
1
6
Order By: Relevance
“…While these attributes generally suggest a depletion of genetic diversity (Ellstrand & Elam 1993), they are not reliable predictors of genetic dynamics (Premoli et al 2001), as is demonstrated by our findings in P. secreta. The rate of seed germinability in endogamous treatments was at least equivalent to that obtained from outcrossing (Fig.…”
Section: Discussioncontrasting
confidence: 52%
“…While these attributes generally suggest a depletion of genetic diversity (Ellstrand & Elam 1993), they are not reliable predictors of genetic dynamics (Premoli et al 2001), as is demonstrated by our findings in P. secreta. The rate of seed germinability in endogamous treatments was at least equivalent to that obtained from outcrossing (Fig.…”
Section: Discussioncontrasting
confidence: 52%
“…Further, Salvador et al (2000) showed that a range in genetic variation of forest tree from low to very high depending upon specific population. Broader area of sampling from geographically distinct populations is the possible cause of high gene diversity in present study (Premoli et al, 2001). …”
Section: Genetic Differentiation/partitioning Of Genetic Diversity Inmentioning
confidence: 68%
“…The genetic structure of plant populations reflects the interactions among different factors, including the long-term evolutionary history of the species, genetic drift, mating system, gene flow and selection (Burgarella et al, 2007;Schaal et al, 1998). Geographically disjunct populations showed higher genetic structure than populations with more continuous distributions (Hamrick and Godt 1996;Premoli et al, 2001). The fragmentation of carob populations associated probably to a limited movement of pollinators and seed dispersal are the main factors affecting gene flow and differentiation among population.…”
Section: Discussionmentioning
confidence: 99%